2010
DOI: 10.1007/s10388-010-0244-6
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragmatic herniation after esophagectomy for carcinoma of the esophagus: a report of two cases

Abstract: Diaphragmatic herniation after esophagectomy for carcinoma of the esophagus is a rare but preventable postoperative complication. For patients with symptoms, surgical repair of the hernia is recommended to prevent the potentially disastrous complications. In patients with asymptomatic hernias, a watchful waiting approach is reasonable. To prevent diaphragmatic herniation, we emphasize the importance of routine narrowing of the hiatus so that the surgeon can introduce three or four fi ngers and recommend awaren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…The incidence rate of postoperative diaphragmatic hernias after esophagectomy is estimated to be between 0.6 and 10% [1,6]. This rate may vary depending on the operative technique, such as When the retrosternal route is used, the hiatus is often closed tightly, and diaphragmatic herniation will occur less frequently [7]. On the other hand, in many Western countries, the mediastinal route is often used for adenocarcinoma of the esophagus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence rate of postoperative diaphragmatic hernias after esophagectomy is estimated to be between 0.6 and 10% [1,6]. This rate may vary depending on the operative technique, such as When the retrosternal route is used, the hiatus is often closed tightly, and diaphragmatic herniation will occur less frequently [7]. On the other hand, in many Western countries, the mediastinal route is often used for adenocarcinoma of the esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…Another study suggested that tissue fragility after neoadjuvant chemoradiation could be strongly related to risk factors for postoperative hiatal hernia [3,7]. Late diaphragmatic hernias are associated with progressive hiatal dilatation secondary to diaphragm weakness or increased intra-abdominal pressure caused by a gibbus deformity [3,7,13].…”
Section: Discussionmentioning
confidence: 99%
“…Although some cases of diaphragmatic hernia after esophagectomy have been reported, the hernia orifice in these cases was located at the hiatus only [ 7 ]. No reports have described the hernia orifice at the pericardium, as in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…Существуют данные, что послеоперационные грыжи диафрагмы могут развиваться только при ор-тотопическом проведении трансплантата, так как при ретростернальном проведении желудочного стебля пищеводное отверстие диафрагмы наглухо ушивается [4]. И хотя у части больных это ослож-нение развивается в раннем послеоперационном периоде, в 2 / 3 случаев послеоперационные диафраг-мальные грыжи выявляются в сроки от 1 до 44 мес и даже через 7 лет после вмешательства [5].…”
Section: рис 2 кт-реконструкция диафрагмальной грыжи слеваunclassified